(untitled) (Hydro Nepal: Journal of Water, Energy and Environment, 2017)
Reliable estimation of in-situ stress state is very important in implementing the shotcrete lined/ unlined tunnels and shafts. The in-situ stress state of the area of concern is mainly governed by the gravity-induced stress, tectonic activity of the earth’s crust and topographic condition of that area. The local tectonic and geological environment such as faulting and shearing activities in general influences the magnitude of tectonic stress level. The Himalayan region is renowned with its active tectonic movement (earthquake activities), which causes accumulation and sudden release of strain energy instigating changes in the stress environment. This paper aims to evaluate in-situ stress state at the Upper Tamakoshi Hydroelectric Project, where shotcrete lined/ unlined headrace tunnel with considerable hydrostatic head is being implemented. A detailed assessment of the in-situ stress state is carried out by using both measured data and three-dimensional numerical analysis using FLAC3D. HYDRO Nepal Journal Journal of Water Energy and Environment Issue: 21, July, 2017 Page: 34-41 Upload Date: July 18, 2017